Localization of partial discharge in the high voltage apparatus - Amir Ghaedi; Mehrdad Mahmoudian; Eduardo M.G. Rodrigues; Rui Melicio (Results in Control and Optimization)
Partial discharges (PD) in high-voltage (HV) devices can be used as indicators of insulation deterioration, often preceding catastrophic failures in power systems. This paper presents a novel approach for locating and identifying PD sources in HV equipment, targeting insulation condition monitoring in power transformers, XLPE cables, and generators. The new technique utilizes the correlation between PD signal energy characteristics to estimate the source location. The effectiveness of the proposed method is validated through selected case studies involving XLPE cables, transformers, and generators. The results demonstrate that the technique can accurately locate PD sources, potentially enhancing the reliability and longevity of HV power equipment. Key contributions of this work include: a comprehensive review of PD detection sensors, with a focus on electrical methods for high-frequency pulse measurement; experimental characterization of PD signals in XLPE cables and transformers, providing insights into their frequency properties; development of a correlation-based algorithm for PD localization, utilizing a database of simulated PD signals; and validation of the proposed method through EMTP-RV simulations and MATLAB signal processing, showing high accuracy in PD source localization. However, the proposed technique has limitations that prevents its generalized which are highlighted in the paper.